Capital Account Liberalization and Economic Growth - Feng, Jie (Université d'Ottawa | University of Ottawa, 2005)
In this paper, I test whether capital account liberalization will lead to higher economic growth by panel cross-country regressions. After reviewing some of the previous literature, I extend the analysis by using three distinct of measures of capital acco